Usulan Perbaikan Desain Kemasan Menggunakan Metode Quality Function Deployment dan House Of Quality - Lucky Irawati; Wiwik Handayani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Quality function deployment is a management tool where customers desires are use a tool for product development. While the house of quality is a tool in the form of a house that connects the wishes of the customer (what) and how a product will be designed and produced to meet customer desires. The research objective to be achieved in this research is to produce a packaging design for banana chips at UD Sumber Rejeki Jombang by using the quality function deployment (QFD) and house of quality (HoQ) methods. In this study, the author uses a descriptive method with a quantitative approach. The results of the QFD analysis research that the highest attribute value for the importance level is “product quality according to the price offered” with a value4.62 and the lowest level of importance is”plastic readiness” with a value of 3.92. the result of the QFD analysis research that the highest attribute value for the level of satisfaction is “product quality according to the price offered” with a value of 4.62 and the lowest value is “variant taste” with a value of 3.3. Keywords : packaging repair, Quality Function Deployment (QFD), House of Quality (HoQ)